The associations of Urinary Neutrophil Gelatinase-associated Lipocalin (NGAL) and Liver-type Fatty Acid Binding Protein (L-FABP) Levels with Hematuria in Children and Adolescents - Youngmin Choi; Joong Hyun Bin; Kyoung Soon Cho; Juyoung Lee; Jin-Soon Suh (Korean Society of Pediatric Nephrology, 2019)
Purpose We sought to determine associations of urinary neutrophil gelatinase-associated lipocalin (NGAL) and liver-type fatty acid-binding protein (L-FABP), known markers of renal injury, with hematuria in children and adolescents. Methods A total of 112 urine samples from 72 patients aged 2 to 18 years with hematuria were enrolled in this study. Urinary concentrations of NGAL and L-FABP were measured by ELISA and compared between subjects with and without proteinuria and between subjects with and without glomerulonephritis diagnosed by renal biopsy. Results Urinary concentrations of NGAL and L-FABP/creatinine (Cr) in subjects with proteinuria were not significantly different from those in subjects without proteinuria. They were not significant different between subjects with and without glomerulonephritis either. However, both concentrations of urinary NGAL and L-FABP/Cr were positively associated with urinary protein to creatinine ratio. Their levels had a tendency to be increased when proteinuria developed at later visits in subjects with hematuria only at initial visits. Conclusion Monitoring urinary NGAL and L-FABP levels in addition to conventional risk factors such as proteinuria and serum creatinine might improve the prediction of renal injury in pediatric patients with hematuria.